MicroRNA-106b promotes colorectal cancer cell migration and invasion by directly targeting DLC1 - Zhang, Guang-jun (J Exp Clin Cancer Res, 2015)
BACKGROUND: Growing evidence suggests that microRNAs (miRNAs) play an important role in tumor development, progression and metastasis. Aberrant miR-106b expression has been reported in several cancers. However, the role and underlying mechanism of miR-106 in colorectal cancer (CRC) have not been addressed. METHODS: Quantitative RT-PCR(qRT-PCR) was performed to evaluate miR-106b levels in CRC cell lines and patient specimens. Cell proliferation was detected using MTT assay, and cell migration and invasion ability were evaluated by wound healing assay and transwell assay. The target gene of miR-106b was determined by qRT-PCR, western blot and luciferase assays. RESULTS: miR-106b was significantly up-regulated in metastatic CRC tissues and cell lines, and high miR-106b expression was associated with lymph node metastasis and advanced clinical stage. In addition, miR-106b overexpression enhances, whereas miR-106b depletion reduces CRC cell migration and invasion. Moreover, we identify DLC1 as a direct target of miR-106b, reveal its expression to be inversely correlated with miR-106b in CRC samples and show that its re-introduction reverses miR-106b-induced CRC cell migration and invasion. Furthermore, survival analyses showed the patients with high mi-106b/low DLC1 had shorter overall survival (OS) and disease-free survival (DFS) rates, and confirmed miR-106b may be an independent prognostic factor for OS and DFS in CRC patients. CONCLUSIONS: Our findings indicate that miR-106b promotes CRC cell migration and invasion by targeting DLC1. This miRNA may serve as a potential prognostic biomarker and therapeutic target for CRC.